2016
DOI: 10.1002/dac.3250
|View full text |Cite
|
Sign up to set email alerts
|

Line of sight model for visible light communication using Lambertian radiation pattern of LED

Abstract: This paper illustrates line of sight model for visible light source and a photodiode in wireless communication. Light-emitting diodes (LEDs) are predominantly used everywhere like in houses and factories as light source due to development in technology of light sources. Haitz's law predicts an exponential rise in light output and efficiency of LEDs over a period of time. Light-emitting diodes are having an average life of 50 000 hours with efficiency of 140 lm/W. Light-emitting diode light sources are used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Bhalerao et al suggested a line of site model by using Lambertian pattern of LED in which they analyzed power distribution of white LED source with a photodiode as a receiver in a room. is investigation completely depends upon the half-power angle of the LED source with the field of view of photodetector and mode number of radiation lobe [19]. Wang et al developed a new theory for the analysis of received power distribution in a generalized indoor VLC system.…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Bhalerao et al suggested a line of site model by using Lambertian pattern of LED in which they analyzed power distribution of white LED source with a photodiode as a receiver in a room. is investigation completely depends upon the half-power angle of the LED source with the field of view of photodetector and mode number of radiation lobe [19]. Wang et al developed a new theory for the analysis of received power distribution in a generalized indoor VLC system.…”
Section: Previous Workmentioning
confidence: 99%
“…e last one is LED sources completely work under the Lambertian radiation Pattern phenomenon. Practically, it is not a compulsion that LEDs follow LRP, e.g., Phosphor-coated multichip LED does not pursue the Lambertian model for the reproduction of luminous intensity pattern [19].…”
Section: Vlc System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Lambertian radiant intensity is featured in the LED is known as Lambert's emission law optics [10]. The law stated that the radiant intensity or luminous intensity observed from an ideal diffusely reflecting surface or ideal diffuse radiator is directly proportional to the cosine of the angle 0 between the direction of the incident light and the surface normal.…”
Section: Simulation Designmentioning
confidence: 99%
“…The viewing angle of the transmitting LEDs can be increased to increase the uniformity of illumination 13,14 . Moreover, it has been reported that smaller field of view (FOV) of receiver leads to more blind spots over the receiving plane and larger FOV makes receiver more susceptible to noise, hence it needs to be chosen wisely for practical applications 15–18 . The channel modeling is also very important for designing an effective VLC system and analyzing its performance 4,19 .…”
Section: Introductionmentioning
confidence: 99%